Architectural Improvement of the Buildings of the Scientific Center for Career Guidance of Creative Youths (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
In this article, the author presents suggestions that serve to strengthen the practical application of theoretical knowledge. Proposals and recommendations on the improvement of the design of innovative creative-production scientific centers for youth career guidance are highlighted.The article deals with the issues of further enrichment of theoretical knowledge of young people, proper formation of scientific research and work on ideas, production of samples, commercialization of developments and presentation to practice. In addition, it sets out the basics of creating great opportunities for young people to put their innovative proposals into practice by jointly designing individual buildings and experimental rooms in each direction regarding the improvement of the design of innovative creative-production scientific centers of young people, to inform young people about interest, motivation and final results. Issues of mobilizing creativity aspirations, and studying the experiences of developed countries, raising innovative centers to the level of state policy for the development of the state, theoretical and practical knowledge being required from young people in a harmonious manner.